CFD Analysis for Aerodynamic Performance Optimization of a Vertical Axis Helical Wind Turbine Using Rigid PVC - Outar Hamza; Ennadafy Hamza; Jammoukh Mustapha; El Khaili Mohamed (E3S Web of Conferences)
In the context of sustainable development, and faced with the dual global threat of the depletion of fossil energy resources and their harmful environmental impact, the use of renewable energies is emerging as a promising alternative. The number of wind turbines being installed around the world is growing rapidly, and research into the aerodynamics of wind turbines has become highly specialised. Computational fluid dynamics (CFD) is used to analyse the effect of loads on the aerodynamic performance of wind turbines. To optimise this performance and ensure greater reliability, it is essential to model the airflow around the turbine. This study focuses on evaluating the first comparative part of the dynamic performance of a vertical axis wind turbine made of innovative bio-composite and rigid PVC, using the finite element method. The simulations revealed that bio-composite blades offer a significant improvement in energy performance compared with rigid PVC blades. In addition, the adoption of bio-composite further reduced the overall carbon footprint of the blades, making them more environmentally friendly. The results of this research underline the superior potential of bio-composites over rigid PVC in the wind energy sector, paving the way for more sustainable technologies.